Preparation and application of porous nitrogen-doped graphene obtained by co-pyrolysis of lignosulfonate and graphene oxide. (January 2015) - Zhao, Hai-Bo; Wang, Wen-Dong; Lü, Qiu-Feng; Lin, Ting-Ting; Lin, Qilang; Yang, Haijun
Highlights: Nitrogen-doped porous graphene was fabricated by co-pyrolysis of LS, GO and urea. Lignosulfonate performed as both dispersant and porogen in the co-pyrolysis process. The porous structure of graphene resulted from the pyrolysis of lignosulfonate. Abstract: Nitrogen-doped graphene with in-plane porous structure was fabricated by simple co-pyrolysis of lignosulfonate and graphene oxide in the presence of urea. Lignosulfonate first performs as a dispersant adsorbed on the surface of graphene oxide to prevent the aggregation of graphene oxide sheets for preparing homogeneous nitrogen-containing precursor, and then acts as a porogen to render graphene sheets with nanopores in the pyrolysis process of the nitrogen-containing precursor. Urea was used as a nitrogen source to incorporate nitrogen atoms into graphene basal plane. The special nanoporous structure combined with nitrogen content of 7.41 at.% endows the nitrogen-doped graphene electrode material with super capacitance up to 170 F g −1, high rate performance, and excellent cycling stability.